A new Hechtia (Bromeliaceae) from the states of Querétaro and Hidalgo, Mexico - Ramírez-Morillo, Ivón M. (Instituto de Ecología, A.C., 2008)
Hechtia lepidophylla is described and illustrated. A complete description including characters of staminate, pistillate, and fruiting plants is included, with details of growth pattern and ecological characteristics, as well as characters to distinguish it from species with similar vegetative and floral characters such as H. argentea, H. glomerata, and H. texensis.